Chronic Insufficient Sleep Has a Limited Impact on Circadian Rhythmicity of Subjective Hunger and Awakening Fasted Metabolic Hormones - McHill, Andrew W.; Hull, Joseph T.; McMullan, Ciaran J.; Klerman, Elizabeth B. (Frontiers in Endocrinology, 2018)
Weight gain and obesity have reached epidemic proportions in modern society. Insufficient sleep – which is also prevalent in modern society – and eating at inappropriate circadian times have been identified as risk factors for weight gain, yet the impact of chronic insufficient sleep on the circadian timing of subjective hunger and physiologic metabolic outcomes are not well understood. We investigated how chronic insufficient sleep impacts the circadian timing of subjective hunger and fasting metabolic hormones in a 32-day in-laboratory randomized single-blind control study, with healthy younger participants (range, 20-34 years) randomized to either Control (1:2 sleep:wake ratio, 6.67 h sleep:13.33 h wake, n=7, equivalent to 8 h of sleep per 24 h) or chronic sleep restriction (CSR, 1:3.3 sleep:wake ratios, 4.67 h sleep:15.33 h wake, n=8, equivalent to 5.6 h of sleep per 24 h) conditions. Participants lived on a ’20 h day’ designed to distribute all behaviors and food intake equally across all phases of the circadian cycle over every 6 consecutive 20 h protocol days. During each 20 h day, participants were provided a nutritionist-designed, isocaloric diet consisting of 45-50% carbohydrate, 30-35% fat and 15-20% protein adjusted for sex, weight and age. Subjective non-numeric ratings of hunger were recorded before and after meals and fasting blood samples were taken within 5 minutes of awakening. Subjective levels of hunger and fasting concentrations of leptin, ghrelin, insulin, glucose, adiponectin, and cortisol all demonstrated circadian patterns; there were no differences, however, between CSR and Control conditions in subjective hunger ratings or any fasting hormone concentrations. These findings suggest that chronic insufficient sleep may have a limited role in altering the robust circadian profile of subjective hunger and fasted metabolic hormones.